MRI-guided focused ultrasound robotic system for the treatment of bone cancer - Menikou, Georgios; Yiallouras, Christos; Yiannakou, Marinos; Damianou, Christakis A. (My University, 2017)
Background: A novel MRI-conditional robot was developed that navigates a focused ultrasound (FUS) transducer. With this robotic system the transducer can access bones. The intended application is pain palliation from bone cancer using thermal ablation using FUS. Methods: The robotic system has four computer-controlled axes (three linear and one angular). The robotic system was manufactured using a digital manufacturing 3D printer, using acrylonitrile butadiene styrene (ABS) plastic. MRI-conditional optical encoders were used to accurately control the robotic system. Results: The robotic system was successfully tested for MRI safety and compatibility, using fast-gradient pulse sequences and a liquid phantom. The robotic system has been tested for its functionality for creating discrete and multiple (overlapping) lesions in a gel phantom. Conclusions: An MRI-conditional FUS robotic system was developed that has the potential to create thermal lesions with the intention of treating bone cancer for the purpose of pain palliation.
Keywords: MRI; Bone; Cancer; Pain; Robot; Ultrasound